Optimized production and characterization of endo-β-mannanase by Aspergillus niger for generation of prebiotic mannooligosaccharides from guar gum - Suresh Nath; Naveen Kango (Scientific Reports)
Abstract Optimized production of Aspergillus niger ATCC 26011 endo-β-mannanase (ManAn) on copra meal resulted in 2.46-fold increase (10,028 U/gds). Purified ManAn (47 kDa) showed high affinity towards guar gum (GG) as compared to konjac gum and locust bean gum with Km 2.67, 3.25 and 4.07 mg/mL, respectively. ManAn efficiently hydrolyzed GG and liberated mannooligosaccharides (MOS). Changes occurring in the rheological and compositional aspects of GG studied using Differential scanning calorimetry (DSC), Thermal gravimetric analysis (TGA) and X-ray diffraction (XRD) revealed increased thermal stability and crystallinity of the partially hydrolyzed guar gum (PHGG). Parametric optimization of the time and temperature dependent hydrolysis of GG (1% w/v) with 100 U/mL of ManAn at 60 °C and pH: 5.0 resulted in 12.126 mg/mL of mannotetraose (M4) in 5 min. Enhanced growth of probiotics Lactobacilli and production of short chain fatty acids (SCFA) that inhibited enteropathogens, confirmed the prebiotic potential of PHGG and M4.